An Accurate Numerical Solution of a Two Dimensional Heat Transfer Problem with a Parabolic Boundary Layer (Journal of Computational Mathematics, 1998)
A singularly perturbed linear convection-diffusion problem for heat transfer in two dimensions with a parabolic boundary layer is solved numerically. The numerical method consists of a special piecewise uniform mesh condensing in a neighbourhood of the parabolic layer and a standard finite difference operator satisfying a discrete maximum principle. The numerical computations demonstrate numerically that the method is $ε$-uniform in the sense that the rate of convergence and error constant of the method are independent of the singular perturbation parameter $ε$. This means that no matter how small the singular perturbation parameter $ε$ is, the numerical method produces solutions with guaranteed accuracy depending solely on the number of mesh points used.